2008
DOI: 10.1161/atvbaha.107.153056
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Activation of Matrix Metalloproteinase 9 and Transforming Growth Factor β in Arterial Elastocalcinosis

Abstract: Objective-Isolated systolic hypertension is associated with increased elastase activity, vascular calcification, and vascular stiffness. We sought to determine the importance of elastase activity and matrix degradation in the development of elastocalcinosis. Methods and Results-Elastocalcinosis was induced in vivo and ex vivo using warfarin. Hemodynamic parameters, calcium deposition, elastin degradation, transforming growth factor (TGF)-␤ signaling, and elastase activity were evaluated at different time point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 42 publications
3
67
0
3
Order By: Relevance
“…However, our histologic analysis of the elastic lamellae in calcifying arteries of rats treated with warfarin to induce elastocalcinosis (30,31,56) did not reveal overt elastin fragmentation (data not shown) in contrast to MGP null arteries. Further, in warfarin- induced calcification, previous studies identified activation of MMP-9 and no induction of serine elastases (22), whereas in the MGP null arteries, the elevated elastase activity is derived from the serine protease adipsin. Together, these results question the role of MGP carboxylation in the regulation of elastolytic activity in VSMCs.…”
Section: Discussionmentioning
confidence: 89%
“…However, our histologic analysis of the elastic lamellae in calcifying arteries of rats treated with warfarin to induce elastocalcinosis (30,31,56) did not reveal overt elastin fragmentation (data not shown) in contrast to MGP null arteries. Further, in warfarin- induced calcification, previous studies identified activation of MMP-9 and no induction of serine elastases (22), whereas in the MGP null arteries, the elevated elastase activity is derived from the serine protease adipsin. Together, these results question the role of MGP carboxylation in the regulation of elastolytic activity in VSMCs.…”
Section: Discussionmentioning
confidence: 89%
“…However, we cannot exclude a possible contribution of severe calcification to vascular stiffness at more advanced stages (such as stage 4 or 5 CKD 22 ) because severe calcification induced by vitamin D 3 plus nicotine or by warfarin plus vitamin K 1 in rat models has been shown to be associated with increased aortic stiffness. 12,23,24 It should be noted that in these 2 animal models, the authors observed an elevation in the ratio of aortic collagen to elastin in association with the vascular calcifications, which may be the result of severe elastocalcinosis inducing destruction of elastic fibers and thus leading to arterial stiffness. 24,25 We did not observe this type of change in the ratio of aortic collagen to elastin; this could explain the absence of a correlation between vascular calcification and vascular stiffness in our present experiments.…”
Section: Discussionmentioning
confidence: 93%
“…Major medial calcifications are certainly an important factor in aortic stiffness alteration. 12 However, the development of mild to moderate calcifications such as those observed in earlier stages of CKD may not necessarily correlate with the development of aortic PWV alterations.…”
mentioning
confidence: 99%
“…During atherogenesis, macrophage-derived elastases, such as elastolytic cathepsins or MMPs (MMP-2 and MMP-9), have been shown to degrade medial elastin, which favors calcification through an increase of elastin polarity that, in turn, enhances elastin affinity for calcium (Sasaki et al, unpublished data, 2011). 86,87 Recently, the data from cathepsin S-deficient mice have provided new insights into the pathobiology of arterial calcification and have aided the investigation of novel therapeutic strategies to reduce the onset of cardiovascular events and, thus, mortality (Table). 88 …”
Section: Atherosclerosis-related Vasa Vasorummentioning
confidence: 99%